Entre pressões e desafios: uma análise sobre a relação entre saúde mental e o trabalho de professores da educação básica - Salustiano, Olívia Borges (Universidade Federal de São Carlos, 2024)
The purpose of this research is to examine the subjective and mental health conditions of teachers who work in the basic education system in the city of São Carlos, located in the interior of São Paulo, and to investigate how such conditions are linked to work circumstances and experiences of the school environment. The interest in this topic emerged from the researcher's empirical observations during her internship at the City Hall of São Carlos, in 2022, in the area of People Management, when she noticed a significant number of medical certificates and licenses related to mental health problems, particularly among workers at the Department of Education. Furthermore, on other occasions, during direct interactions with these education professionals, arising from their various internship assignments, it was again found that their complaints often included high levels of stress and emotional overload. The methodological approach essentially consisted of two phases. The first phase involved the application of an online questionnaire, with the aim of measuring the degree of stress perceived in the work environment by teachers regarding various aspects. The second phase consisted of semi-structured interviews, divided into three parts: 1) interviewee profile, 2) professional experiences and 3) personal life and health, with questions prepared considering the most relevant aspects identified in the questionnaire. The interviews aimed to explore both aspects of the participants' professional and personal lives, analyzing again the issue of stress at work, emotional burden and perceived pressures, in addition to identifying possible health problems related to professional practice in the interviewees' view. It was evidenced that teachers in the municipal basic education network in São Carlos-SP face several challenges in their working conditions that directly affect their mental well-being. Among the main obstacles identified are excessive workload, low payment, lack of valuation of the profession, poor physical structure of the work environment and lack of material resources.
Between pressures and challenges: an analysis of the relationship between mental health and the work of basic education teachers
Keywords: Trabalho docente; Saúde mental; Subjetividade; Educação básica; Professor; Teaching work; Mental health; Subjectivity; Basic education; Teacher; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS